Electricity generation in microbial fuel cell (MFC) by ralstonia spp. isolated from rice paddy field soil - Fakhriah binti Fakhirruddin (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Microbial fuel cell (MFC) is an alternative approach in generating renewable energy by utilising bacteria that will oxidise organic or inorganic substrates, producing electrons yielded as electrical energy. Dependency on fossil fuel resources for energy generation lead to possibility of imbalance in demand and supply for electricity in a long run. Different species of exoelectrogenic bacteria capable of generating significant amount of electricity in MFC has been identified, using various organic compounds for fuel. Soil sample taken from rice paddy field has been proven to contain exoelectrogenic bacteria, thus electricity generation using mixed culture originally found in the soil, and pure culture isolated from the soil was studied. This research successfully isolated the exoelectrogenic bacterial species from the rice paddy field soil responsible for energy generation. The growth of bacteria isolated from the MFC was observed by measuring the optical density (OD), cell density weight (CDW) and viable cell count. Mixed bacterial species found in paddy field soil generated maximum power of 77.62 µW and 0.70 mA of current. In addition, the research also showed that the pure bacterium in rice paddy field soil could produce maximum power and current at 51.32 µW and 0.28 mA, respectively. The electricity generation by both pure and mixed culture was limited to the small scale of this research. For a better result of electricity generation, the research should be upscaled. Identity of bacteria isolated from rice paddy field soil was checked through 16S rRNA method, and a gram-negative, rod-shaped bacterial species was identified. The isolated bacterium belongs to the genus Ralstonia spp. and is in the same evolutionary branch to Ralstonia mannitolytica strain LMG6866. The species is commonly found in moist environment and respire anaerobically in soil with high nitrate content. In this study, the bacterial species was assimilated with acetate which naturally present in the soil and the optimum temperature for the bacteria to grow and produce significant power output was 27°C. Ralstonia spp. is a novel exoelectrogenic bacterial strain identified from this research, for previously there is no report claiming the species as exoelectrogen.